Effects of Social Participation and Its Diversity, Frequency, and Type on Depression in Middle-Aged and Older Persons: Evidence From China - Wang, Jiahui; Xu, Jiao; Nie, Yizhen; Pan, Pochuan; Zhang, Xin; Li, Ye; Liu, Huan; Liang, Libo; Gao, Lijun; Wu, Qunhong; Hao, Yanhua; Shah, Saleh (Frontiers in Psychiatry, 2022)
Background Depression is one of the greatest public health problems worldwide. The potential benefit of social participation (SP) on mental health has been widely acknowledged. Nevertheless, few studies have used propensity score matching (PSM) to reduce the influence of data bias and confounding variables. This study explored the effect of social participation on depression among middle- and old-aged Chinese persons through a PSM method, considering the frequency, type and quantity of SP. Effects were compared among different age groups, genders, and places of residence. Methods The datasets were obtained from the 2018 wave of the China Health and Retirement Longitudinal Study. A total of 9404 respondents aged 45 and above were included in the study. PSM and ordinary least squares methods were used to estimate the effect of social participation on depression. Results PSM estimation results showed that SP had a significantly positive effect by decreasing depression scores (p < 0.001) by 0.875-0.898 as compared with persons without SP. All types of SP had a significantly positive effect (p < 0.001) and participating in community activities had the largest effect (β = -1.549 to -1.788, p < 0.001). Higher frequency of participation and more types of SP promoted lower depression scores; subgroup analyses revealed that the promotion effect was significantly greater among females, those aged ≥ 75 years, and those living in urban areas. Conclusion PSM indicated that SP could alleviate the depression of middle-aged and elderly Chinese persons. Targeted measures should be adopted to promote SP and thereby improve mental health and promote healthy and active aging.